2002
DOI: 10.1021/ac025787l
|View full text |Cite
|
Sign up to set email alerts
|

Dependence of Ion Selectivity on Ordered Orientation of Neutral Carriers in Ion-Sensing Membranes Based on Thermotropic Liquid Crystals

Abstract: Thermotropic liquid-crystalline compounds were applied as membrane materials (membrane solvent and neutral carrier) for neutral carrier-type ion sensors to investigate how the ordered arrangement of neutral carriers affects the property of the resulting ion sensors. Nematic, smectic, and cholesteric liquid-crystalline compounds were used as the membrane solvents and crown ether derivatives with a molecular structure similar to the liquid-crystalline solvent as the K+ neutral carriers. Polarized IR spectroscopy… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
16
0

Year Published

2004
2004
2014
2014

Publication Types

Select...
5
1
1

Relationship

2
5

Authors

Journals

citations
Cited by 25 publications
(16 citation statements)
references
References 13 publications
0
16
0
Order By: Relevance
“…In the membrane systems using NPOE, which is a conventional solvent for ion-sensing PVC membranes, the electrode also showed good sensor properties. Although the linear ranges for the PTFE-impregnated membranes are slightly narrow compared with those of the ISEs based on their corresponding pure liquid-crystalline membranes, 3,4 there seems to be no problem in the analysis of K + for real samples, such as biomedical samples or environmental samples. These results indicate that liquid-crystalline membrane ISEs, in which a PTFE porous membrane was used as the supporting material, respond to K + activity changes with a Nernstian response in any of the nematic, smectic, and isotropic liquid states.…”
Section: Emf Responses To K + Activity Changes For Ises Based On Ptfementioning
confidence: 99%
See 1 more Smart Citation
“…In the membrane systems using NPOE, which is a conventional solvent for ion-sensing PVC membranes, the electrode also showed good sensor properties. Although the linear ranges for the PTFE-impregnated membranes are slightly narrow compared with those of the ISEs based on their corresponding pure liquid-crystalline membranes, 3,4 there seems to be no problem in the analysis of K + for real samples, such as biomedical samples or environmental samples. These results indicate that liquid-crystalline membrane ISEs, in which a PTFE porous membrane was used as the supporting material, respond to K + activity changes with a Nernstian response in any of the nematic, smectic, and isotropic liquid states.…”
Section: Emf Responses To K + Activity Changes For Ises Based On Ptfementioning
confidence: 99%
“…We have previously reported that thermotropic liquid-crystalline compounds are very promising as functional membrane solvents for ISEs. 3,4 The ion-sensor property could be controlled by the orientation of the membrane components. In other words, liquid-crystalline compounds can induce an ordered molecular orientation of other organic components in the liquid-crystal phase.…”
Section: Introductionmentioning
confidence: 99%
“…The pure liquid membrane was incorporated into a plastic tip of an adjustable pipette (Q-110, Quality Science Plastics), which has an inner diameter of 0.5 mm, for the capillary-type ion-selective electrode. 3,4 The electrodes were built up as follows. To a capillary, 10 μL of 1 × 10 -3 M KCl aqueous solution as an internal solution was injected.…”
Section: Preparation Of Ion-sensing Membranesmentioning
confidence: 99%
“…In the case of compound 3, which is able to form a nematic liquid crystal phase, it was not possible to observe the surface of membranes due to the high fluidicity. Therefore, compound 4, which is able to form a less fluidic phase (smectic liquid crystal), was employed here as the membrane solvent, because it possesses similar structural and sensor properties 4,5 to those of compound 3. The content of compound 2 in the membranes was 5.0 wt%, because no clear AFM images were observed when the content of compound 2 was 1.0 wt%.…”
Section: Afm Imagesmentioning
confidence: 99%
See 1 more Smart Citation